Pengaruh Supervisi Akademik, Budaya Sekolah dan Kepuasan Kerja terhadap Kinerja Guru SMPN Kecamatan Pandih Batu dan Kahayan Hilir Kabupaten Pulang Pisau - Destri Yermina; Aslamiah Aslamiah; Ahmad Muhyani Rizalie (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to analyze the influence of academic supervision, school culture, and teacher job satisfaction on teacher performance at SMPN Pandih Batu and Kahayan Hilir Districts, Pulang Pisau District. This research approach is quantitative. The population of this study consisted of all SMPN teachers in Pandih Batu and Kahayan Hilir Districts, Pulang Pisau Regency with a total of 171 teachers. Through sampling using proportional random sampling techniques, a sample of 120 people was obtained. The data collection technique uses a questionnaire distributed to the sample. Analysis of research results using descriptive statistics, regression test, t-test (partial), path analysis, and coefficient of determination using SPSS Windows Version 29.0. The results of the research show that there is an influence between: (1) academic supervision on teacher performance of 0.120, (2) school culture on teacher performance of 0.100, (3) job satisfaction on teacher performance of 0.119, (4) academic supervision on job satisfaction of 0.119. 1.149, (5) school culture on job satisfaction of 0.482, (6) academic supervision on teacher performance through job satisfaction of 0.136, (7) school culture on performance teachers through job satisfaction of 0.057. In conclusion, there is a significant direct and indirect influence between academic supervision, school culture, and job satisfaction on the performance of State Middle School teachers in Pandih Batu and Kahayan Hilir Districts, Pulang Pisau District. Keywords: Academic Supervision, Job Satisfaction, School Culture, Teacher Performance 3) Sedangkan bagi peneliti selanjutnya hendaknya dapat menggunakan hasil penelitian ini sebagai rujukan dan referensi untuk melakukan penelitian yang masih berkaitan. Kata kunci : Supervisi Akademik, Budaya Sekolah, Kepuasan Kerja, Kinerja Guru